The Use of Social Media As an Educational Tool for Students - Laela Worotikan; Karin Kirey Laurencia Rangubang; All Papuko; Anastasya Debora Christoffel; Gracesella Ester Eklesia Lasut; Muhammad Fahjry Sabate (Syntax Corporation Indonesia, 2025)
This study analyzes the use of social media as a learning tool for university students. The main objective of this study is to assess the effectiveness of social media in enhancing education and to identify the challenges encountered in its implementation. The method used is a qualitative case study, including interviews with students and lecturers, as well as content analysis of social media platforms used in education. The findings show that social media can improve relationships and collaboration among students but also faces challenges related to time management and information accuracy. This research proposes strategies to maximize the effectiveness of social media in education. Social media has become an integral part of students' daily lives, offering more than just a platform for communication and entertainment. In recent years, it has evolved into a powerful educational tool, enabling students to access learning materials, collaborate with their peers, and engage with academic content in innovative ways.